Analysis of Uterine Rupture in Pregnancy at a Tertiary Care Hospital - Shakya, Beemba (Nepal Journal of Obstetrics and Gynaecology, 2019)
Aims: To analyze patients with uterine rupture in pregnancy. Methods: This was a cross-sectional retrospective study undertaken at Paropakar Maternity and Women’s Hospital. Two years’ medical records of uterine rupture between 14 April 2017 and 13 April 2019 were reviewed. Information on patient characteristics, age, parity, mode of previous deliveries, onset of labour spontaneous or induced, type and site of rupture, maternal and perinatal outcome, management and complications associated with it were retrieved and was analyzed using SPSS version 16.0. Results: Among 29 uterine rupture cases, majority of cases occurred in 25-29 years (48.3%), para1 (79.3%) and unbooked cases (72.4%). Most of them occurred in previous scar 23(79.3%); rupture was complete in 13 and incomplete in 10 cases. Six (20.6%) were unscarred uterine rupture. Rupture repair was done in 24(82.7%) and peripartum hysterectomy (subtotal hysterectomy) in 5(17.2%) cases. The most common complications were postpartun hemorrhage (55.2%), hospital stay >7 days (55.2%), blood transfusion (48.3%) and ICU admission (41.3%). There was no maternal mortality. Perinatal death was 15 (51.7%)-13 stillbirths and 2 neonatal deaths. Conclusions: Majority of the uterine rupture occurred in previous scar (79.3%). Most of the cases underwent repair of the uterus (82.7%) and remaining were peripartum hysterectomy (17.2%). There was no maternal mortality. However, perinatal mortality occurred in 51.7%. Keywords: peripartum hysterectomies, previous scar, repair of uterus, uterine rupture.